THE UNIQUE NARRATIVE STYLE OF O. HENRY IN AMERICAN LITERATURE (World Bulletin of Education and Learning, 2025)
This article explores the distinctive narrative style of O. Henry, one of the most influential short story writers in American literature. His works are characterized by witty humor, situational irony, vivid characterization, and moral insight. The study aims to analyze how O. Henry’s stylistic devices including unexpected endings, colloquial dialogue, and humanistic themes shaped the development of the American short story tradition. Using literary and stylistic analysis, the article demonstrates that O. Henry’s originality lies in his ability to transform ordinary experiences into profound moral reflections.
Keywords: O. Henry, irony, narrative style, short story, humor, realism, American literature.